Strategi Manajemen Pendidikan Islam dalam Mewujudkan Budaya Mutu Berkelanjutan pada Madrasah di Provinsi Lampung - Firdaus Firdaus; Nur Widiastuti; Suci Hartati (Atmosfer: Jurnal Pendidikan, Bahasa, Sastra, Seni, Budaya, dan Sosial Humaniora, 2026)
This study aims to explore Islamic educational management strategies in fostering a sustainable quality culture in madrasahs in Lampung Province amid increasing global quality demands and limited institutional capacity. A qualitative multiple case study was conducted at MAS Al-Khairiyah Natar and MAS Sunanul Huda. Data were collected through semi-structured interviews with 12 participants, participant observation, and document analysis. The data were analyzed using the interactive model of Miles, Huberman, and Saldaña, while trustworthiness was ensured through triangulation, member checking, and an audit trail. The findings identified six major themes: leadership as the key driver of quality culture, continuous evaluation, internalization of Islamic values, stakeholder collaboration, contextual organizational differences, and structural challenges related to technology and funding. The results show that quality culture has become institutionalized beyond the influence of individual principals, challenging the view that its sustainability depends primarily on leadership continuity. The study contributes to the development of quality culture in Islamic education by integrating Total Quality Management, Islamic values, and local social capital. It also highlights the need to strengthen collaborative evaluation mechanisms and increase governmental support to reduce technological and financial disparities in madrasahs.